2018
DOI: 10.12659/msm.909651
|View full text |Cite
|
Sign up to set email alerts
|

Neogambogic Acid Suppresses Receptor Activator of Nuclear Factor κB Ligand (RANKL)-Induced Osteoclastogenesis by Inhibiting the JNK and NF-κB Pathways in Mouse Bone Marrow-Derived Monocyte/Macrophages

Abstract: BackgroundNeogambogic acid (NGA) is used in traditional Chinese medicine. The aim of this study was to investigate the effects of NGA on gene signaling pathways involved in osteoclastogenesis in mouse bone marrow-derived monocyte/macrophages (BMMs) and on bone resorption in vitro.Material/MethodsPrimary mouse BMMs were cultured with increasing concentrations of NGA. Real-time polymerase chain reaction was used to study the expression of mRNAs corresponding to gene products specific to receptor activator of NF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…LPS stimulated activation of p38 MAPK/NF-κB signaling, and inactivation of p38 MAPK/NF-κB signaling alleviated LPS-induced cardiac insufficiency [ 21 ]. Silica-induced up-regulation of p-p38 in macrophages was decreased by neogambogic acid [ 11 ], and neogambogic acid reduced p-JNK and p-NF-κB in receptor activator of nuclear factor κB ligand-induced mice [ 22 ]. This study revealed that neogambogic acid down-regulated protein expression of p-p38, p-JNK and p-NF-κB in heart tissues of septic mice, suggesting that neogambogic acid might alleviate sepsis induced cardiomyopathy through inactivation of p38 MAPK/NF-κB signaling.…”
Section: Discussionmentioning
confidence: 99%
“…LPS stimulated activation of p38 MAPK/NF-κB signaling, and inactivation of p38 MAPK/NF-κB signaling alleviated LPS-induced cardiac insufficiency [ 21 ]. Silica-induced up-regulation of p-p38 in macrophages was decreased by neogambogic acid [ 11 ], and neogambogic acid reduced p-JNK and p-NF-κB in receptor activator of nuclear factor κB ligand-induced mice [ 22 ]. This study revealed that neogambogic acid down-regulated protein expression of p-p38, p-JNK and p-NF-κB in heart tissues of septic mice, suggesting that neogambogic acid might alleviate sepsis induced cardiomyopathy through inactivation of p38 MAPK/NF-κB signaling.…”
Section: Discussionmentioning
confidence: 99%
“…ZA treatment Frontiers in Pharmacology frontiersin.org can down-regulate JNK phosphorylation in a dose-dependent manner. However, ZA cannot significantly affect the phosphorylation levels of p38 and ERK, suggesting that ZA can specifically inhibit RANKL-induced JNK phosphorylation during osteoclast differentiation (Jin et al, 2018;Huang et al, 2019;Sun et al, 2020;Cheng et al, 2021;Huang et al, 2022). ZA can inhibit RANKL-induced downstream expression of c-Jun, c-Fos and nuclear factor of activation of T cells-1 (NFATc1).…”
Section: Zoledronic Acid Inhibits Osteoclast Differentiationmentioning
confidence: 99%
“…Both the mitogen-activated protein kinases (MAPK) and NF-κB signaling pathways are closely related to osteoclast differentiation. The MAPK pathway, including extracellular signal-regulated kinase (ERK), c-Jun N-terminal kinase (JNK), and p38, is critical for regulation of osteoclast differentiation ( Jin et al, 2018 ; Huang et al, 2019 ; Peng et al, 2021 ). ZA treatment can down-regulate JNK phosphorylation in a dose-dependent manner.…”
Section: Zoledronic Acid Inhibits Osteoclast Differentiationmentioning
confidence: 99%
“…GA and NGA are two active compounds found in Garcinia species, which exhibit immune-enhancing, anti-inflammatory, antitumor, and proapoptotic activities (Wang et al, 2011; Chen et al, 2015; Zhang et al, 2016; Jin et al, 2018). Especially in the aspects of anti-inflammatory and anti-tumor, it has been found that gamoic acid can inhibit many cell signaling pathways, such as nuclear factor-kappa B (nf-κb), tumor necrosis factor-α (TNF-α), and iNOS (Pandey et al, 2016; Sun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%